Work-family conflict and the professional quality of life and their sociodemographic characteristics among nurses: a cross-sectional study in Tehran, Iran - Reza Biabani Dilmaghani; Baharam Armoon; Ladan Fattah Moghaddam (BMC, 2022)
Abstract Background Nurses are exposed to work-family conflict (WFC) due to specific occupational conditions, such as exposure to patients and shift work, which can affect the professional quality of life (ProQoL). The aim of the present study was to determine the relationship between different levels of work-family conflicts and professional quality of life and their sociodemographic characteristics among the nurses in two hospitals in Tehran, Iran. Methods This cross-sectional study included 234 nurses from two hospitals. Data were collected using a three-part questionnaire, including items related to nurses' demographic characteristics, the WFC questionnaire, and the ProQoL questionnaire. Results There was a significant positive correlation between conflict in terms of time and behavior with compassion satisfaction and between the three types of conflict with job burnout (p < 0.05). The results indicate that the WFC and ProQoL scores and the mean WFC were higher among women, people who had a disabled family member, and nurses who worked equal to or more than 175 hours a month. Regarding the dimensions of ProQoL, the mean compassion satisfaction was lower among people who lived with their parents, people who had a second job had a child younger than one-year-old, and a disabled family member had higher means of job burnout. Also, those who had younger children experienced less PTSD. Furthermore, the mean of WFC and burnout among single nurses was significantly lower than among married and divorced/widowed nurses. Additionally, the mean of WFC and burnout among nurses living in rental houses and nurses reporting the level of satisfying relationships with co-workers as 'bad' were significantly more than for other nurses. Conclusion Stable mental and emotional conditions are of great importance for nurses to provide safe and quality services to their patients. The results also revealed that nurses' compassion satisfaction and job burnout were associated with different types of conflict. The WFC of nurses is related to their ProQoL and affects their job satisfaction and burnout. Reducing conflict may improve the nurses' satisfaction and thus improve patient care and healthcare services.